a) Vì \(0,\left(3\right)=\dfrac{3-0}{9}=\dfrac{3}{9}=\dfrac{1}{3}\) và \(-0,4\left(2\right)=-\dfrac{42-4}{90}=-\dfrac{38}{90}=-\dfrac{19}{45}\) nên:
\(0,\left(3\right)+3\dfrac{1}{3}-0,4\left(2\right)=\dfrac{1}{3}+\dfrac{10}{3}-\dfrac{19}{45}=\dfrac{11}{3}-\dfrac{49}{45}\)
\(=\dfrac{165-19}{45}=\dfrac{146}{45}\)
b) Vì \(0,\left(5\right)=\dfrac{5-0}{9}=\dfrac{5}{9}\) và \(0,\left(2\right)=\dfrac{2-0}{9}=\dfrac{2}{9}\) nên:
\(\left[0,\left(5\right).0,\left(2\right)\right]:\left(3\dfrac{1}{3}:\dfrac{33}{25}\right)=\left(\dfrac{5}{9}.\dfrac{2}{9}\right):\left(\dfrac{10}{3}.\dfrac{25}{33}\right)=\dfrac{10}{81}:\left(\dfrac{110.25}{33}\right)\)
\(=\dfrac{10}{81}.\dfrac{33}{110.25}=\dfrac{3}{81.25}=\dfrac{1}{27.25}=\dfrac{1}{675}\)